1997
DOI: 10.1007/s11661-997-0222-3
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and mechanical properties of sputter-deposited Cu1−x Ta x alloys

Abstract: The microstructures and mechanical properties of a family of sputter-deposited Cu 1Ϫx Ta x (0 Ͻ x Ͻ 0.18) alloys have been investigated. The as-deposited microstructures for all film compositions consisted of a polycrystalline, face-centered-cubic (fcc) Cu matrix, with varying levels of Ta in solid solution, plus a very high density of discrete, 1 to 3 nm, fcc Ta particles. Decreased deposition temperature (Ϫ120 ЊC vs 100 ЊC) increased the level of Ta in solid solution. After annealing (900 ЊC for 1 hour) the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 16 publications
2
11
0
Order By: Relevance
“…It increases regularly with the aluminium concentration and will reach a maximum over the concentration 33.36 at.%Al. This evolution is very close to that already observed for sputtered thin films Cu-Ta [5]. The extrapolation of the microhardness of sputtered pure copper gives an approximate value of 5000 MPa, it exceeds of about 3500 MPa to that of bulk pure copper measured under the same conditions ( Table 4).…”
Section: Microhardnesssupporting
confidence: 87%
See 2 more Smart Citations
“…It increases regularly with the aluminium concentration and will reach a maximum over the concentration 33.36 at.%Al. This evolution is very close to that already observed for sputtered thin films Cu-Ta [5]. The extrapolation of the microhardness of sputtered pure copper gives an approximate value of 5000 MPa, it exceeds of about 3500 MPa to that of bulk pure copper measured under the same conditions ( Table 4).…”
Section: Microhardnesssupporting
confidence: 87%
“…Another equation was found for Cu solid solution in sputtered Al-Cu prepared almost in the same conditions [4]: a (nm)=0.3615+2.4 Â 10 À4 x, the apparition of the second phase g-Al 4 Cu 9 is announced for 25 at.%Cu. A similar evolution is found for copper solid solution in Cu-0-18 at.%Ta thin films deposited at À120 C [5] and has the form: a (nm)=0.3612+1.8 Â 10 À4 y, where y is Ta atoms concentration (at.%Ta). But fine particles of Ta were found in dilute deposited Cu-Ta films.…”
Section: Lattice Parametersupporting
confidence: 71%
See 1 more Smart Citation
“…Wang et al reported that the microstructure of Cu-Ta alloy film, 12 m thick, remained submicrometer grain size and the Ta particles precipitated to grain boundary after annealing at 900°C. 14 However, as an interconnect material, there is no detailed literature regarding the interfacial reaction and diffusion of Cu-Ta alloy films ͓referred to as Cu͑Ta͒ hereafter͔ with its neighboring materials. The diffusion of Cu into SiO 2 may cause degradation of devices at high temperature or high voltage.…”
mentioning
confidence: 99%
“…• C [20]. This parameter increases with Ta composition in the films where the structure is two phases as a copper matrix in which are distributed fine particles of tantalum.…”
Section: Lattice Parameter Of Coppermentioning
confidence: 99%